The Evolution of Policies for the Resource Utilization of Livestock Manure in China - Haoyu Lin; Hongchao Jiao; Hai Lin; Xuanguo Xu (Agriculture)
With the continuous development of animal husbandry, the harmless handling and resource utilization of livestock manure has gradually become a bottleneck problem in sustainable agriculture and livestock production in China. This study evaluates the policies related to manure handling and utilization in different economic development periods in China. The decreased pollutant discharge from livestock manure indicates the effectiveness of the strategy aiming to encourage the construction of manure treatment facilities and resource utilization in cropland and to establish a sound legal system for pollutant discharge. New policies and measures should be introduced to promote the coupling of intensive livestock breeding and crop planting, with the direction of nutrient management planning and the incorporation of a service platform for the resource utilization of manure. Technological innovation in green livestock breeding should be supported by policies to achieve source reduction in pollutants in breeding waste.